2012
DOI: 10.1634/theoncologist.2011-0323
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Use of Low Molecular Weight Heparin Monotherapy for First-Line Treatment of Venous Thromboembolism in Advanced Cancer

Abstract: Background. Evidence-based treatment guidelines recommend low molecular weight heparin (LMWH) monotherapy for cancer-associated venous thromboembolism (VTE). This analysis assessed the first-line treatment strategies for VTE in patients with advanced solid tumors.Methods. Using administrative data from advanced lung, prostate, colon, or breast cancer patients diagnosed between January 2000 and December 2007 at four HMOs with integrated delivery systems, patients with an inpatient or outpatient VTE diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Similar observations were made from a previous retrospective, longitudinal cohort study in 1089 cancer patients with diagnosed VTE showing that the proportion of cancer patients receiving LMWH as a first-line therapy for the prevention of VTE recurrence had increased from 8% in 2000 to 31% in 2008 even though this remains insufficient [17]. Furthermore, another study in Switzerland has shown that only 39% of cancer patients with VTE were planned for long-term treatment with LMWH [18].…”
Section: Discussionsupporting
confidence: 78%
“…Similar observations were made from a previous retrospective, longitudinal cohort study in 1089 cancer patients with diagnosed VTE showing that the proportion of cancer patients receiving LMWH as a first-line therapy for the prevention of VTE recurrence had increased from 8% in 2000 to 31% in 2008 even though this remains insufficient [17]. Furthermore, another study in Switzerland has shown that only 39% of cancer patients with VTE were planned for long-term treatment with LMWH [18].…”
Section: Discussionsupporting
confidence: 78%
“…More recently a trend towards a superior efficacy in reducing the relative risk of VTE recurrence was shown with the LMWH tinzaparin compared to VKA [19]. Despite the evidence [20][21][22], there are substantial reports from observational studies of insufficient adherence to established clinical practice guidelines [23][24][25][26][27]. Thrombosis Research 144 (2016) [85][86][87][88][89][90][91][92] Recent studies have shown that long-term LMWH were well accepted by patients and physicians tended to underestimate patients' ability to accept long-term treatment with LMWH [28].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for the use of LMWHs in the long-term treatment of cancer-associated VTE. Many patients receive VKAs instead, and if LMWHs are given, they are often underdosed or terminated prematurely [18,19,20,21,22,23,24,25,26,27,28,29]. With the advent of NOACs, the preference of the guidelines for LMWHs over any of these newer agents will be further challenged.…”
Section: Introductionmentioning
confidence: 99%